2022
DOI: 10.1108/apjml-07-2021-0493
|View full text |Cite
|
Sign up to set email alerts
|

Robo-advisor based on unified theory of acceptance and use of technology

Abstract: PurposeFollowing the advancement of financial technology (FinTech) in modern society to assist investment decisions, robo-advisers had become widely used in mean-variance analyses to allow investors to formulate efficiently diversified investment portfolios. However, the concept of robo-advisers is new, and few studies have addressed issues related to them. To help readers to better understand robo-advisor adoption by a wide range of potential customers, this study explores integrated models of the attitudes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Particularly, contradictory findings have been reported in the context of FinTech. Rahim et al [52] found an insignificant influence on consumer perception, which conflicts with the conclusion of Yeh et al [53] who confirmed the relationship. These wildly divergent findings demonstrated the need to investigate how effort expectancies affect users' intentions to use FinTech services.…”
Section: Effort Expectancymentioning
confidence: 77%
See 2 more Smart Citations
“…Particularly, contradictory findings have been reported in the context of FinTech. Rahim et al [52] found an insignificant influence on consumer perception, which conflicts with the conclusion of Yeh et al [53] who confirmed the relationship. These wildly divergent findings demonstrated the need to investigate how effort expectancies affect users' intentions to use FinTech services.…”
Section: Effort Expectancymentioning
confidence: 77%
“…According to these studies, it is a crucial concept in the analysis of improved information system usage. The degree to which FinTech meets customer expectations is essential to fully understand its usefulness [23,52,53]. Therefore, consumers may be more likely to use these services if they believe FinTech would significantly improve their financial performance.…”
Section: Performance Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…The results have produced a comprehensive analysis of the current patterns and trends in robo-advisers based on 11 research articles. Generally, regarding the year of publication, an article was published in 2019 and 2020 (Belanche et al, 2019;Fan & Chatterjee, 2020), two articles were published in 2021 (Au et al, 2021;Seiler & Fanenbruck, 2021;Cheng, 2021), and six articles were published in 2022 (Figà-Talamanca et al, 2022;Flavián et al, 2022;Isaia & Oggero, 2022;Jain & Raman, 2022;Kumari & Devi, 2022;Yeh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to gather supplementary data about the topic to enhance investors' comprehension of their complete potentials in addressing diverse financial-technology concerns. Yeh et al (2022) have also noted that the emergence of robo-advisers represents a relatively recent phenomenon, resulting in a limited body of research dedicated to exploring the associated concerns and challenges. Kraiwanit et al (2022) have conducted a study examining the impact of robo-adviser designs and mechanics on individuals' economic decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%